Effectiveness of Content-Based Instruction (CBI) Model Based on Multimedia Presentations for Improving the Japanese Language Learning Outcomes of STIKES Bethesda Tomohon Students - Susanti Chornelly Aror; Ruty Jacoba Kapoh (Journal of Japanese Language Education and Linguistics, 2024)
This research aims to examine students' learning outcomes using the Content-Based Instruction (CBI) model facilitated by Multimedia Presentations, and to assess the efficiency of this approach in enhancing students' proficiency in Japanese. This study's background indicates that numerous students struggle with learning Japanese due to pedagogical approaches that prioritize memory and are predominantly traditional in nature. This research employs a pre-experimental design utilizing an Intact-Group Comparison methodology. Data acquisition Observation and test administration (Pretest-Posttest). Statistical analysis: Descriptive and inferential statistics. Forty pupils from STIKES BETHESDA were sampled. This study demonstrates that the Content-Based Instruction (CBI) learning approach utilizing Multimedia Presentations enhances Japanese language proficiency among students. The result is that the Content-Based Instruction (CBI) paradigm utilizing Multimedia Presentations is demonstrably beneficial in enhancing students' Japanese language learning outcomes.